[And justice for all ; No place like home ; Talking heads II [videorecording] - Lazaro, Cheche (The Probe Team ; [episode no.143], 1991)
Unsolved cases on the death hazing victims Lenny Villa, Ateneo, Joselito Hernandez, U.P. Baguio and Joselito Manga, PMI; Experiences of abused and neglected children; People who used their voices for a living.